Attitude in disaster reports in Indonesian newspaper: A critical discourse analysis - Namira, Ade; Setia, Eddy; Mono, Umar; Rangkuti, Rahmadsyah; Fithriani, Rahmah (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
Examining disaster reports in Indonesia is critical, as it provides essential insights into people perceptions and reactions to the frequent natural disasters. Disaster reports were examined through its communicative element including attitude to see the viewpoints of the newspaper towards disaster reports. The objectives of this research are to categorize attitudes, explain how attitudes are realized, and explain why attitudes are realized in disaster reporting in Indonesian newspaper, especially The Jakarta Post (TJP). Using Critical Discourse Analysis (CDA) as the analytical framework, a qualitative method was employed. The data is analyzed using Martin and White's theory of appraisal (2005). A corpus of 14 TJP newspaper articles on Indonesian natural disasters published in 2021 is broken down into clauses denoting attitude. The results of the study indicate: 1) there are three different attitude types, with appreciation being the most prevalent and having a predominately negative polarity, 2) the attitude realization reveals that TJP is the most dominant appraiser, followed by the authorities, and 3) the realization is attributed to two themes namely self-claimed recognition and neglect of self-failure, and one tone multiple perspectives which means negative attitudes dominantly voiced by different appraisers. The themes reveal the newspaper's concealed ideology points to a narrative of critique and disillusionment, which may shape the readers' understanding of the disasters and the associated societal responses.